2011
DOI: 10.1001/archinternmed.2011.399
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacist Care in the Management of Cardiovascular Disease Risk Factors

Valérie Santschi

Abstract: Pharmacist-directed care or in collaboration with physicians or nurses improve the management of major CVD risk factors in outpatients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
129
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(149 citation statements)
references
References 56 publications
9
129
1
4
Order By: Relevance
“…Lifestyle advice should be provided at both interventions and followup stage of NMS. Previous systematic reviews and meta-analysis have demonstrated that community pharmacists can significantly improve blood pressure control of hypertensive patients by giving advice related to medications as well as advice on lifestyle [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle advice should be provided at both interventions and followup stage of NMS. Previous systematic reviews and meta-analysis have demonstrated that community pharmacists can significantly improve blood pressure control of hypertensive patients by giving advice related to medications as well as advice on lifestyle [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] It also builds on existing knowledge of public trust in pharmacists more widely, as evidenced in narrative and systematic reviews of pharmacy based public health activities. [10][11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…14 Since that time, the impact of pharmacist involvement in the management and outcomes in patients with hypertension has been demonstrated in multiple settings showing improvements in blood pressure control and other cardiovascular risk factors. 15,16 Pharmacists have notably been reported to have significant impact on hypertension control rates when electronically engaged with patients for consultation in combination with web-based education and home blood pressure monitoring. 17 Most recently, home blood pressure telemonitoring along with pharmacistprovided management and dosage adjustments have significantly improved hypertension control in patients.…”
Section: Discussionmentioning
confidence: 99%